Study of foulants quantification of protein-based ultrafiltration using chitosan/silver nanoparticles polyethersulfone membranes - Nur Mahirah Chik@Ismail (Universiti Malaysia Terengganu, 2022)
Fouling limits the process performance in membrane technology applications. Biofouling, on the other hand, is the major contributing factor in membrane fouling phenomena. When dealing with protein-based solutes, it is essential to control biofouling occurrence caused by bacterial growth on the membrane surfaces and in pores. AgNP is able to inhibit bacteria growth and improve the permeability of polymeric membrane while chitosan can improve membrane hydrophilicity and possess antibacterial properties. Thus, silver nanoparticles (AgNP) and chitosan were chosen as bacteria inhibitors due to their remarkable antibacterial properties. This study was carried out to determine the effect of AgNP, chitosan, and a combination of both on fouling occurrence during protein-based ultrafiltration. These experiments were conducted by using the native Polyethersulfone (PES) membrane in comparison with the PES-Ag membrane, PES-Chitosan membrane, and PES-Ag-Chitosan membrane at a controlled condition where 150ppm bovine serum albumin (BSA) was applied as a model protein. A resistance-in-series model was adopted to determine the magnitude of four major resistances that govern fouling mechanisms namely membrane (Rm), adsorption (Ra), pore plugging (Rg), and cake formation (Rc) resistances to obtain better insights into fouling occurrences. The resistances magnitude was significantly reduced and arranged in a sequence of Rg>Rm>Ra>Rc for the PES-Ag-Chitosan membrane. Foulant weight was significantly reduced by 56% for the PES-Ag-Chitosan membrane as compared to PES-Chitosan and PES-Ag membranes which marked a reduction of 53% and 50% respectively using iv Thermogravimetric analysis (TGA) analysis. Based on the fouling quantification analysed and resistance-in-series computed for BSA ultrafiltration in dead-end configuration, it was proposed that the modification of PES membrane by incorporating AgNP and surface modification via Chitosan simultaneously is favourable to be implemented to mitigate biofouling. It indicates that AgNP and chitosan have a synergistic effect in overcoming the fouling contributed by both - solutes depositions and bacterial growth.